C‐reactive protein increases with gestational age during pregnancy among Chinese women. Issue 4 (11th February 2016) - Mei, Zuguo; Li, Hongtian; Serdula, Mary K.; Flores‐Ayala, RAFAEL C.; Wang, Linlin; Liu, Jian‐Meng; Grummer‐Strawn, Laurence M.
Abstract : Objective: To examine the concentration of C‐reactive protein (CRP) in relation to gestational weeks during pregnancy among Chinese women. Methods: From a randomized control trial of prenatal supplementation with folic acid, iron‐folic acid, and multiple micronutrients in China, we examined 834 pregnant women with CRP measured initially between 5 and 20 weeks and at follow‐up between 28 and 32 weeks gestation. We calculated and plotted CRP geometric means by gestational weeks. The same analysis was repeated for women who had normal pregnancies (624 women) by excluding women with stillbirth, preterm, small for gestational age, body mass index <18.5 kg/m 2 or >30 kg/m 2 at enrollment, and hypertension or anemia during pregnancy. Results: We observed a significant positive trend between log‐transformed CRP and gestational age from 5 to 20 weeks and from 28 to 32 weeks both in the full sample and in the subset of women who had normal pregnancies. CRP geometric mean was 0.81 mg/l at 5–7 weeks of gestation, 2.85 mg/l at 19–20 weeks of gestation, and 3.89 mg/l at 32 weeks of gestation. A similar increasing trend in the CRP median or percentage of elevated CRP were also observed. Conclusion: We concluded that CRP increased with gestational age among healthy Chinese women who delivered healthy infants. Am. J. Hum. Biol. 28:574–579, 2016. © 2016 Wiley Periodicals, Inc.